Tiny House - Elizabeth Turnbull (Oz, 2009)
Elizabeth Turnbull is a graduate student at the Yale School of Forestry and Environmental Studies. In 2008 she set out to build her own residence in New Haven. The staff conducted this interview in April 2009.